Effects of intracerebroventricular MOTS-c infusion on thyroid hormones and uncoupling proteins - Bahar, Mehmet Refik; Tekin, Suat; Beytur, Asiye; Onalan, Ebru Etem; Ozyalin, Fatma; Colak, Cemil; Sandal, Suleyman (Springer Heidelberg, 2023)
This study was conducted to determine the possible effects of intracerebroventricular MOTS-c infusion on thyroid hormones and uncoupling proteins (UCPs) in rats. Forty male Wistar Albino rats were divided into 4 groups with 10 animals in each group: control, sham, 10 and 100 mu M MOTS-c. Hypothalamus, blood, muscle, adipose tissues samples were collected for thyrotropin-releasing hormone (TRH), UCP1 and UCP3 levels were determined by the RT-PCR and western blot analysis. Serum thyroid hormone levels were determined by the ELISA assays. MOTS-c infusion was found to increase food consumption but it did not cause any changes in the body weight. MOTS-c decreased serum TSH, T3, and T4 hormone levels. On the other hand, it was also found that MOTS-c administration increased UCP1 and UCP3 levels in peripheral tissues. The findings obtained in the study show that central MOTS-c infusion is a directly effective agent in energy metabolism.
Keywords: MOTS-c; Thyroid hormones; Energy use; UCP1; UCP3